Penerapan Kegiatan Drum Band dalam Mengembangkan Kecerdasan Musikal pada Anak Usia 5-6 Tahun di TK Ceria SKB Pangkalpinang - Sulistianingsih, Meidiana (ICEJ : Islamic Childhood Education Journal, 2024)
There are many intelligences that every child has. This intelligence includes diverse abilities (multiple intelligences). Music is closely related to intelligence. By learning music, children will be able to increase their intelligence. Musical intelligence is the main intelligence in children which includes sensitivity to rhythm, pitch patterns, timbres, and forms of musical emotional expression. There are still many educational institutions that still do not pay attention to the development of children’s musical intelligence. One of them is to develop children’s musical intelligence through drum band activities. The aim of this research is to find out how drum band activities are implemented in developing the musical intelligence of children aged 5-6 years at Kindergarten Ceria SKB Pangkalpinang. This research is field research using qualitative descriptive methods. The research location is TK Ceria SKB Pangkalpinang. The data sources for this research are the principal and teachers of the Ceria SKB Pangkalpinang Kindergarten. Data collection techniques were obtained through observation, interviews and documentation. The data analysis technique in this research consists of three stages, namely, data reduction, data presentation and drawing conclusions. The results of the research and discussion on the application of drum band activities in developing the musical intelligence of children aged 5-6 years in accordance with the planning stages, the teacher prepares the drum band activity schedule, the teacher prepares the equipment for the drum band activities, the implementation stages, namely, the teacher prepares the place for the drum band activities, The teacher introduces drum band playing equipment, the teacher conveys the rules for playing drum band activities, the teacher models drum band playing activities, children do drum band activities, and the evaluation stage is, the teacher carries out an evaluation assessment. The results of implementing drum band activities in developing the musical intelligence of children aged 5-6 years are that children are able to play musical instruments, children are able to follow the rhythm of music with drum band instruments, and children are able to recognize the notes of various kinds of songs.